Cardiovascular and microvascular outcomes of glucagon-like peptide-1 receptor agonists in type 2 diabetes: a meta-analysis of randomized controlled cardiovascular outcome trials with trial sequential analysis - Xiaowen Zhang; Fei Shao; Lin Zhu; Yuyang Ze; Dalong Zhu; Yan Bi (BMC, 2018)
Abstract Background Efficacy trials showed that glucagon-like peptide-1 receptor (GLP1R) agonists reduced metabolic risk factors in addition to glucose lowering, but the cardiovascular and microvascular efficacy of this drug class remains to be determined. We aimed to evaluate the overall cardiovascular and microvascular efficacy of GLP1R agonists by performing a meta-analysis with trial sequential analysis. Methods Randomized controlled, cardiovascular outcomes trials including at least 2000 patient-years' follow-up and 100 composite cardiovascular events were included. Trial sequential analysis (TSA) was performed and the quality of evidence was graded. Results Thirty-three thousand four hundred fifty-seven patients and 4105 cardiovascular events from 4 large trials were included. GLP1R agonists were associated with a statistically significant reduction in risks for all-cause mortality (hazard ratio [HR]: 0.88, 95% CI: 0.81 to 0.95; number needed to treat [NNT]: 286 person-years), cardiovascular mortality (HR: 0.87, 95% CI: 0.79 to 0.96; NNT: 412 person-years), stroke (HR: 0.87, 95% CI: 0.76 to 0.98; NNT: 209 person-years) and the composite adverse cardiovascular outcome (MACE; HR: 0.91, 95% CI: 0.85 to 0.96; NNT: 241 person-years). The magnitude of benefit on MACE was attenuated in patients with a history of congestive heart failure (HR: 0.96, 95% CI: 0.85 to 1.08 with; HR: 0.87, 95% CI: 0.77 to 1.00 without). The risks for hospitalization for heart failure and myocardial infarction were not significantly different. The quality of the evidence was deemed as moderate to high based on GRADE approach. TSA provided firm evidence for a 10% reduction in all-cause mortality, a 15% reduction in MACE, and lack of a 15% reduction in hospitalization for heart failure, but evidence remains inconclusive for cardiovascular mortality and myocardial infarction. GLP1R agonists numerically reduced the rates for nephropathy but the risk for retinopathy was similar. Conclusions Meta-analysis with trial sequential analysis suggested that GLP1R agonists significantly reduced the risk for all-cause mortality and composite cardiovascular outcomes, but the reduction of cardiovascular mortality remains to be confirmed.